Detecção de Leifsonia xyli subsp xyli em mudas-pré-brotadas de cana-de-açúcar - Oliveira, Danielle de (Universidade Federal de São Carlos, 2017)
The first great change in recent years of the Brazilian sugarcane industry occurred when mechanical harvest replaced the manual cuttings of burned canes. The second transformation has started with mechanization of planting materials thanks to new methodologies such as pre-sprouted cane (MPB in Portuguese). To ensure the success of this innovation, however, is paramount the use of clean seed cane, especially against ratoon stunting disease, caused by the fastidious bacterium Leifsonia xyli subsp. xyli (Lxx). This disease is considered the most important and the only means of transmission to new area is the use of contaminated propagative materials. Therefore, the purpose of this work was to develop a routine diagnostic test for early detection of Lxx in MPB seedlings. In the first assay, four previously published pair of primers, Cxx ITSf#5/Cxx ITSr#5, Cxx1/Cxx2, C2F/C2R, LX23SF/LX23SR, was challenged under the conditions described, as well as, our own modifications against adult diseased sugarcane with various concentrations of Lxx. In the second assay, two of the best primers/conditions were tested against MPB seedlings of 45 and 60 days of age derived from Lxx-contaminated materials. Our result showed primers Cxx ITSf#5/Cxx ITSr#5 run under our modifications was the recommended since Lxx was detected in all 52 MPB seedlings of 45 days resulted from propagative materials contaminated with 109 up to 106 UFC/mL.
Detection of Leifsonia xyli subsp xyli in presprouted seedcane
Keywords: Raquitismo-das-soqueiras; Diagnóstico; Disseminação; Cana-de-açucar; CIENCIAS AGRARIAS